Legal Analysis Regarding Donation Fraud Through Online Media - Agustini, Shenti; Situmeang, Ampuan; Agustianto, Agustianto (JUSTISI, 2024)
Indonesia already has regulations in place to regulate digital fraud matter, but these regulations have not been able to accommodate current needs. The novelty in this research is that this research discusses current issues where fraud is carried out using sophisticated technology, namely through cyberspace, even fraud can also be carried out for the reason of a good cause, namely making a donation. The purpose of this study is first, to analyze the laws governing online donation fraud. Second, to identify cases or phenomena regarding fraud that occur online and resolve these cases. then through this research can produce a recommendation or legal solution will be found in overcoming the online fraud case. The method in this study is normative juridical which uses a statutory approach consisting of laws, namely Law Number 9 of 1961 concerning Collection of Money or Goods, Government Regulation Number 29 of 1980 concerning Implementation of Contribution Collection. Then the data collection technique is through literature studies and studies through fraud cases that have occurred. Based on the results of the research, it was found that online donation fraud cases are currently being tried using the criminal law code and the law on information and electronic transactions. However, the two regulations have different elements of fraud and sanctions. Even though Indonesia has a regulation that specifically regulates the collection of donations, however, these two regulations do not regulate the forms of donations that can be made online.